Medium voltage power cable and application
Patent Information
- Application Number
- CN202611450468.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-18
- Publication Date
- 2026-10-27
AI Technical Summary
但在外护套层发生机械破损后,水分仍可能透过破损点进入电缆内部,而现有外护套材料本身通常不具备遇水自密封能力,难以在破损后主动阻断水分侵入
[0028]本发明至少具有如下技术效果之一:1.本发明的阻燃粒子在ADP核表面依次形成PDA层、MgAl-LDH层和AA-HEMA聚合物层,PDA层为后续无机层沉积提供界面,MgAl-LDH层与ADP和Mg(OH)2共同改善阻燃功能层的燃烧行为,外侧交联聚合物层用于在限制含磷组分热水浸出的同时赋予粒子局部吸水膨胀能力,所得阻燃功能层在所述试验条件下表现出一定的阻燃性能和湿热性能保持。
Smart Images

Figure CN122991752A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of cable technology, specifically to a medium-voltage power cable and its application. Background Technology
[0002] Medium-voltage power cables are crucial power transmission carriers in urban power transmission and distribution, tunnels, utility tunnels, and shafts. These environments are typically characterized by humidity, confinement, poor ventilation, and even prolonged water immersion, placing high demands on the flame retardancy, water resistance, environmental friendliness, and long-term operational reliability of the cable sheath. The sheath not only needs to slow flame spread, reduce heat release and smoke density under fire conditions, but also must prevent moisture from penetrating longitudinally or radially along the cable during normal operation and in case of damage, thus avoiding a decline in insulation performance. With increasingly stringent requirements for halogen-free, low-smoke, and low-toxicity materials, traditional halogen-containing flame-retardant sheath materials are gradually being replaced by halogen-free flame-retardant polyolefin materials.
[0003] Currently, halogen-free flame-retardant polyolefin sheaths typically use metal hydroxides such as magnesium hydroxide and aluminum hydroxide as flame retardants. These flame retardants only achieve ideal flame-retardant effects at high filler contents, but high filler contents often lead to a significant decrease in the tensile strength, elongation at break, and other mechanical properties of the sheath material, limiting their application in cable outer sheaths. To reduce the amount of metal hydroxides used, existing technologies introduce organophosphorus flame retardants such as aluminum diethylphosphonate in combination with metal hydroxides, utilizing the synergistic effect of phosphorus and magnesium to improve flame-retardant efficiency. However, organophosphorus flame retardants tend to migrate and precipitate gradually from the sheath matrix under long-term damp heat, not only reducing flame-retardant durability but also potentially affecting the cable surface condition and other layer structures. To address this issue, existing technologies have attempted to encapsulate or microencapsulate the flame retardants, for example, using polymer shells, inorganic oxide shells, or hydrotalcite barrier layers to inhibit flame retardant migration. However, most of these coating structures primarily function as single barrier structures, and they still fall short in terms of effective flame retardant release, compatibility with polyolefin matrices, and overall performance balance.
[0004] On the other hand, medium-voltage power cables typically have a water-blocking layer to prevent moisture from penetrating longitudinally along the cable. A common water-blocking layer is a water-blocking tape containing highly absorbent resin. However, after mechanical damage to the outer sheath, moisture can still enter the cable through the damaged point. Existing outer sheath materials generally lack self-sealing capabilities upon contact with water, making it difficult to actively prevent moisture intrusion after damage. Furthermore, some existing modified materials containing hydrophilic organic components have compatibility issues with polyolefin matrices, limiting their practical application in cable outer sheaths.
[0005] In summary, even when using phosphorus-containing flame retardants and metal hydroxides to improve the halogen-free flame retardant performance of existing medium-voltage power cables, problems such as leaching of phosphorus-containing components under high-temperature and humid conditions, decreased mechanical properties after high sheath filling, and easy diffusion of moisture along the cracks and longitudinal direction of the cable after mechanical cracks occur in the outer sheath are still possible. Therefore, it is necessary to provide a medium-voltage power cable that reduces the leaching of phosphorus-containing components under high-temperature and humid conditions while improving radial sealing and longitudinal water-blocking capabilities after sheath damage. Summary of the Invention
[0006] To address the aforementioned problems, the present invention provides a medium-voltage power cable comprising, from the inside out, a conductor, a conductor shielding layer, an insulation layer, an insulation shielding layer, a semi-conductive water-resistant tape, a metal shielding layer, an inner sheath, an armor layer, a water-blocking layer, and an outer sheath, wherein the outer sheath comprises, from the inside out, a flame-retardant functional layer and an outer protective layer.
[0007] Based on 100 parts by weight of linear low-density polyethylene (LLDPE) and ethylene-vinyl acetate copolymer (EVA), the flame-retardant functional layer comprises: 58-62 parts LLDPE, with the balance being EVA; 30-38 parts flame-retardant particles; 45-52 parts KH-550 surface-modified magnesium hydroxide; 5.5-6.5 parts maleic anhydride-grafted polyethylene; 0.25-0.35 parts antioxidant 1010; 0.25-0.4 parts antioxidant 168; 0.5-0.8 parts calcium stearate; and 2-3 parts carbon black masterbatch.
[0008] The flame-retardant particles include an aluminum diethylphosphonate (ADP) core, a polydopamine (PDA) interlayer coated on the surface of the ADP core, a MgAl-LDH (magnesium aluminum layered double hydroxide) layer deposited on the surface of the PDA interlayer, and an AA-HEMA polymer layer formed by in-situ polymerization on the surface of the MgAl-LDH layer and bonded thereto, which is a copolymer of pre-partially neutralized acrylic acid (AA) and hydroxyethyl methacrylate (HEMA).
[0009] The PDA intermediate layer is cross-linked with genipin; the MgAl-LDH layer is surface functionalized with KH-570.
[0010] The thickness of the flame-retardant functional layer accounts for 68% to 75% of the total thickness of the outer sheath layer.
[0011] The water-blocking layer is a water-blocking tape containing sodium polyacrylate superabsorbent resin.
[0012] Preferably, the EVA has a vinyl acetate content of 18%–28% and a melt flow rate of 3–8 g / 10 min at 190°C and 2.16 kg; the LLDPE has a melt flow rate of 1–3 g / 10 min at 190°C and 2.16 kg; the maleic anhydride-grafted polyethylene has a grafting rate of 0.8%–1.2%; and the carbon black masterbatch has a carbon black mass fraction of 40%–50%.
[0013] Preferably, the D50 of the ADP core is 5-10 μm; the molar ratio of Mg to Al in the MgAl-LDH layer is (2.4-2.6):1; the AA neutralization degree of the AA-HEMA polymer layer is 48%-52%, and the mass ratio of AA to HEMA is 1:(0.6-0.8) based on the mass of AA before neutralization, and it is crosslinked with polyethylene glycol diacrylate (PEGDA) at a mass of 1.5%-2.0% of the total mass of AA and HEMA.
[0014] Preferably, based on 100 parts by weight of LLDPE and EVA, the outer protective layer comprises: 70-85 parts of LLDPE, with the remainder being EVA; 0.2-0.4 parts of antioxidant 1010, 0.2-0.4 parts of antioxidant 168, 0.3-0.8 parts of calcium stearate, and 5-6 parts of carbon black masterbatch.
[0015] Preferably, the substrate of the water-blocking tape is a polyester fiber nonwoven fabric, and the coating is an acrylic-sodium acrylate copolymer with a thickness of 0.3-0.5 mm; the free water absorption ratio of the water-blocking tape in deionized water is 15-40 times, the expansion height at a water absorption time of 30 s is 1.5-4.0 mm, and the water absorption under a pressure of 0.1 MPa is not less than 8 times the dry mass.
[0016] This invention also provides a method for preparing a medium-voltage power cable, comprising the following steps: vacuum drying flame-retardant particles at 60-70°C until the moisture content is ≤0.2%; drying KH-550 surface-modified magnesium hydroxide at 80-90°C until the moisture content is ≤0.3%; based on 100 parts by weight of LLDPE and EVA, mixing 30-38 parts of the dried flame-retardant particles with 10-15 parts of EVA, all maleic anhydride-grafted polyethylene, 0.1-0.2 parts of antioxidant 1010 and 0... 0.1-0.2 parts of antioxidant 168 are premixed and then vacuum dried again until the moisture content is ≤0.05% to obtain a pre-dispersed material. Then, 58-62 parts of LLDPE, the remaining EVA, the remaining antioxidant 1010, the remaining antioxidant 168, 0.5-0.8 parts of calcium stearate, and 2-3 parts of carbon black masterbatch are added from the main feed port of the twin-screw extruder. The pre-dispersed material and the dried KH-550 surface-modified magnesium hydroxide are added from the middle and rear side feed ports. The temperature in each zone of the twin-screw extruder is adjusted. The flame-retardant functional layer material is obtained by melt blending and granulation at 130–160℃, with the actual melt temperature not exceeding 165℃; 70–85 parts of LLDPE, 15–30 parts of EVA, 0.2–0.4 parts of antioxidant 1010, 0.2–0.4 parts of antioxidant 168, 0.3–0.8 parts of calcium stearate, and 5–6 parts of carbon black masterbatch are melt-blended, with a total of 100 parts of the linear low-density polyethylene and ethylene-vinyl acetate copolymer; the outer protective layer material is then extruded onto the conductor. A shielding layer, an insulation layer, and an insulating shielding layer are co-extruded and cross-linked to form a wire core. A semi-conductive water-resistant tape is wrapped around the wire core, followed by a metal shielding layer. An inner sheath is then extruded over the metal shielding layer. An armor layer is then wrapped over the inner sheath, and a water-blocking layer is wrapped around the armor layer, with an overlap rate of ≥15%. Finally, the flame-retardant functional layer material and the outer protective layer material are co-extruded to form an outer sheath layer at an extrusion temperature of 140–165°C. The flame-retardant functional layer is located inside the outer protective layer, resulting in the medium-voltage power cable.
[0017] Preferably, the preparation method of the flame-retardant particles includes the following steps: S1, by weight, 10 parts of ADP are subjected to air jet milling and classification to make D50 5-10 μm; the classified ADP is surface silanized and modified with 0.15-0.25 parts of KH-550 in 30-40 parts of ethanol / water mixed solvent, filtered after reaction, washed 2-4 times with ethanol / water mixture, and vacuum dried at 60-70℃ for 10-14 h to obtain ADP core.
[0018] S2. Disperse the ADP core obtained in S1 in 180-220 parts of Tris buffer; add 0.6-0.8 parts of dopamine hydrochloride, stir for 12-16 h at 20-25 °C in contact with air, so that dopamine oxidizes and polymerizes on the surface of the ADP core to form a PDA intermediate layer. Filter, wash until the supernatant is clear and free PDA is removed, then redisperse the particles in 180-220 parts of deionized water, add 0.02-0.03 parts of genipin for crosslinking for 4-6 h, wash again to obtain ADP@PDA particles.
[0019] S3. Disperse the ADP@PDA particles obtained in S2 in 180–220 parts of deionized water to obtain a particle dispersion. Dissolve 0.9–0.95 parts of Al(NO3)3·9H2O and Mg(NO3)2·6H2O calculated according to the Mg / Al molar ratio of 2.4–2.6:1 in 60–80 parts of deionized water to obtain a metal salt mixed solution. Prepare an alkaline solution containing 1–1.5 mol / L NaOH and 0.1–0.2 mol / L Na2CO3, with the actual amount of alkaline solution added determined by pH feedback. Under N2 protection and at 60–65℃, add the metal salt mixed solution and alkaline solution dropwise in parallel to the particle dispersion, and stabilize the pH at 9.3–9.7 by adjusting the alkaline solution flow rate. After the addition is complete, age the solution, wash until the filtrate is nearly neutral, and vacuum dry at 60–80℃ to obtain ADP@PDA@MgAl-LDH particles.
[0020] S4. The ADP@PDA@MgAl-LDH particles obtained in S3 are surface-functionalized with 0.1-0.15 parts of KH-570, then dispersed in 80-120 parts of deoxygenated water. N2 is passed through the water for 20-30 minutes to remove oxygen, and the temperature is raised to 60-65℃. The AA is pre-neutralized with a 25%-35% NaOH solution to a neutralization degree of 48%-52%. Based on the AA before partial neutralization, it is mixed with HEMA at a mass ratio of 1:(0.6-0.8). The total mass of AA and HEMA is 1.2 to 1.6 parts. PEGDA is added at 1.5% to 2% of the total mass of AA and HEMA to obtain a monomer solution. The monomer solution and ammonium persulfate aqueous solution are added dropwise to the particle dispersion to carry out in-situ polymerization reaction. The addition time is 1.5 to 2 hours. After the addition is completed, the reaction continues for 2 to 3 hours. After the reaction is completed, the mixture is filtered and washed until the pH of the washing solution is 6.5 to 7.5. The mixture is then vacuum dried at 60 to 70°C until the moisture content is no higher than 0.2% to obtain the flame retardant particles.
[0021] Preferably, in S1, the mass ratio of ethanol to water in the ethanol / water mixed solvent is 3:1; the pH is adjusted to 4.5-5.5 with dilute acetic acid; KH-550 is pre-hydrolyzed for 20-40 min before ADP is added; the reaction temperature is 50-60℃; and the reaction time is 2-3 h. In S2, the Tris buffer is prepared by tris(hydroxymethyl)aminomethane and hydrochloric acid, with a concentration of 10-30 mmol / L and a pH of 8.3-8.5.
[0022] Preferably, in step S3, the metal salt mixture and alkali solution are added dropwise in two parallel streams: the first dropwise addition of 50% metal salt mixture and alkali solution takes 1–1.5 hours, maintaining a pH of 9.3–9.7, and is aged for 2–3 hours before washing and redispersing the particles in 180–220 parts of deionized water; the second dropwise addition of the remaining metal salt mixture and alkali solution takes 1–1.5 hours, maintaining a pH of 9.3–9.7, and is aged for 4–6 hours; in step S4, KH-570 is first pre-hydrolyzed in an ethanol / water mixture at pH 4.5–5.5 for 20–40 minutes, and then surface functionalized by constant temperature stirring at 50–60°C for 3–4 hours; the ammonium persulfate aqueous solution has a mass concentration of 5%–15%, and the amount of ammonium persulfate is 0.5%–1% of the total mass of AA and HEMA.
[0023] Preferably, the medium-voltage power cable is used in damp or potentially water-immersed environments such as tunnels, pipe corridors, and shafts, in order to balance flame retardancy and water resistance.
[0024] Under weakly alkaline conditions and in contact with air, dopamine can undergo oxidative self-polymerization and deposit on the surface of ADP particles to form a PDA interlayer. The catechol groups, quinone groups, and nitrogen-containing groups in the PDA interlayer can be Mg... 2+ And Al 3+ Providing certain adsorption or coordination sites is beneficial for the nucleation and deposition of MgAl-LDH on the particle surface. Genipin can undergo cross-linking reactions with amino-containing groups in the PDA interlayer, which helps to improve the stability of the PDA interlayer in subsequent processing.
[0025] After KH-570 treatment, carbon-carbon double bonds capable of participating in free radical polymerization can be introduced onto the MgAl-LDH surface. Under ammonium persulfate initiation conditions, partially neutralized AA and HEMA polymerize on the particle surface and in the adjacent region, forming a cross-linked polymer coating layer bound to the particle surface under the action of PEGDA. The carboxylate groups in the partially neutralized AA endow the polymer layer with water absorption capacity, HEMA is used to adjust the hydrophilicity and flexibility of the polymer layer, and the cross-linked structure formed by PEGDA helps to reduce polymer dissolution and limit excessive expansion. Maleic anhydride-grafted polyethylene, as a compatibilizer, helps to improve the dispersion and interfacial bonding of the particles in the LLDPE / EVA matrix.
[0026] When the outer sheath is intact, the outer protective layer reduces direct contact between moisture and the inner flame-retardant functional layer. When a through-crack forms in the outer sheath, the flame-retardant particles exposed on the crack wall can contact the moisture entering the crack. The outer AA-HEMA cross-linked polymer absorbs water and undergoes localized expansion, thus helping to reduce the effective water-passing cross-section of the crack and lower the leakage rate. This effect is a radial auxiliary sealing at the crack and does not mean that the original structure and mechanical properties of the outer sheath are completely restored. The water-blocking strip located outside the armor layer absorbs water and expands after moisture enters, helping to limit the axial diffusion of moisture along the cable.
[0027] ADP, MgAl-LDH, and surface-modified Mg(OH)₂ can collectively influence the combustion process of the material through different pathways. Upon heating, ADP participates in the inhibition of gas-phase free radicals and the formation of phosphorus-containing residual structures in the condensed phase; Mg(OH)₂ undergoes dehydration and absorbs heat upon heating, forming magnesium-containing inorganic residues; MgAl-LDH releases moisture and gases generated from the carbonate-containing system upon heating, forming inorganic oxide residues. These processes help reduce the heat release during combustion and improve the char barrier properties. Combining the oxygen index, vertical combustion, and cone calorimetry results, it can be concluded that this composite system improves the combustion behavior of the flame-retardant functional layer material under the stated experimental conditions.
[0028] The present invention has at least one of the following technical effects: 1. The flame-retardant particles of the present invention form a PDA layer, a MgAl-LDH layer and an AA-HEMA polymer layer sequentially on the surface of the ADP core. The PDA layer provides an interface for subsequent inorganic layer deposition. The MgAl-LDH layer, together with ADP and Mg(OH)2, improves the combustion behavior of the flame-retardant functional layer. The outer cross-linked polymer layer is used to give the particles local water absorption and swelling ability while restricting the leaching of phosphorus-containing components in hot water. The resulting flame-retardant functional layer exhibits certain flame-retardant properties and moisture heat retention under the test conditions.
[0029] 2. The outer sheath of this invention adopts a double-layer structure of a flame-retardant functional layer and an outer protective layer. The flame-retardant functional layer is located inside the outer protective layer, and the outer protective layer is located on the outside. When a through-crack occurs in the outer sheath, the hydrophilic polymer layer in the flame-retardant functional layer can absorb water and swell, thereby helping to reduce the effective water ingress channel at the crack.
[0030] 3. The water-blocking strip outside the armor layer of this invention absorbs water and expands after moisture enters, thus limiting the longitudinal diffusion of moisture along the cable. The crack-blocking auxiliary sealing of the flame-retardant functional layer and the longitudinal water-blocking effect of the water-blocking strip act on different stages of water ingress, thereby improving the flame-retardant and water-blocking performance of medium-voltage power cables in humid or potentially immersion environments. Attached Figure Description
[0031] Figure 1 This is a schematic diagram of the cross-sectional structure of the medium-voltage power cable of the present invention;
[0032] Figure 2 This is a schematic diagram of the hierarchical structure of the flame-retardant particles of the present invention.
[0033] In the diagram: 1. Conductor; 2. Conductor shielding layer; 3. Insulation layer; 4. Insulation shielding layer; 5. Semiconductor resistive water tape; 6. Metal shielding layer; 7. Inner protective layer; 8. Armoring layer; 9. Water-blocking layer; 10. Flame-retardant functional layer; 11. Outer protective layer; 12. AA-HEMA polymer layer; 13. MgAl-LDH layer; 14. PDA intermediate layer; 15. ADP core. Detailed Implementation
[0034] The present invention will now be described in detail through specific embodiments. However, these illustrative embodiments are for purposes and uses only to illustrate the invention and do not constitute any limitation on the actual scope of protection of the invention, nor are they intended to limit the scope of protection of the invention to these embodiments. All equivalent transformations or simple substitutions made based on the substantive content of this application should fall within the scope of protection of this application. For parameter ranges not mentioned, intermediate values are selected. Furthermore, for mass percentages or weight percentages not explicitly stated or mentioned, they generally refer to the final concentration after addition.
[0035] The singular forms “for,” “or,” “a,” “any,” and “the” used in this application are intended to include the plural forms unless the context clearly indicates otherwise.
[0036] In the following examples, unless otherwise stated, the raw materials used meet the following conditions: the melt flow rate was determined according to GB / T 3682.1-2018, and the test conditions were 190℃ and 2.16kg; the EVA used was commercially available EVA with a VA content of 26% and a melt flow rate (MFR, 190℃ / 2.16kg) of 5g / 10min; the LLDPE was MFR 2g / 10min and density 0.920g / cm³. 3 Commercially available LLDPE; maleic anhydride-grafted polyethylene is commercially available MAH-g-PE with a grafting rate of 1.0% and an MFR of 2.5 g / 10 min; KH-550 surface-modified magnesium hydroxide is a commercially available product with D50 = 1.5 μm, KH-550 coating amount of 1.2%, and moisture content of 0.2%; the D50 was determined by laser diffraction particle size analyzer, with ethanol as the dispersion medium and an ultrasonic dispersion time of 3 min.
[0037] Example
[0038] Example 1
[0039] A1. Preparation of flame retardant particles: S1. By weight, 10 parts of ADP were air-jet milled and classified to achieve D50=7μm; 0.2 parts of KH-550 were added to 35 parts of ethanol / water mixed solvent (ethanol to water mass ratio of 3:1), the pH was adjusted to 5 with dilute acetic acid, and pre-hydrolyzed for 30 min; the classified ADP was added, and the mixture was stirred at 55℃ for 2.5 h, filtered, washed 3 times with ethanol / water mixture, and vacuum dried at 65℃ for 12 h to obtain the ADP core.
[0040] S2. Disperse the obtained ADP cores in 200 parts of Tris buffer (tris(hydroxymethyl)aminomethane-hydrochloric acid system, concentration 20 mmol / L, pH 8.4), add 0.7 parts of dopamine hydrochloride, stir for 14 h at 23 °C with open air contact, centrifuge at 4000 r / min for 5 min, and wash with deionized water until the supernatant is clear; redisperse the particles in 200 parts of deionized water, add 0.025 parts of genipin, crosslink at 35 °C for 5 h, centrifuge at 4000 r / min for 5 min, and wash with deionized water to obtain ADP@PDA particles.
[0041] S3. Disperse the obtained ADP@PDA particles in 200 parts of deionized water to obtain a particle dispersion; dissolve 0.925 parts of Al(NO3)3·9H2O and 1.581 parts of Mg(NO3)2·6H2O (Mg to Al molar ratio 2.5:1) in 70 parts of deionized water to obtain a mixed metal salt solution; prepare a solution containing 1.2 mol / L NaOH and 0.15 mol / L... Na2CO3 alkaline solution; under N2 protection and 63℃ conditions, the metal salt mixture and alkaline solution were added dropwise to the particle dispersion in two parallel streams: the first deposition was 50% metal salt mixture solution, with a corresponding amount of alkaline solution added simultaneously, over a period of 1.25 h. The pH was stabilized at 9.5 by adjusting the alkaline solution flow rate, and the particles were aged for 2.5 h. After centrifugation at 4500 r / min for 8 min, the particles were washed with deionized water until the filtrate was nearly neutral, and the particles were redispersed in 200 parts of deionized water. The second deposition was 1.25 h of adding the remaining metal salt mixture and the corresponding alkaline solution, maintaining the pH at 9.5. After the addition was completed, the particles were aged for another 5 h. After aging, the particles were centrifuged at 4500 r / min for 10 min, washed until the filtrate was nearly neutral, and then vacuum dried at 70℃ for 12 h to obtain ADP@PDA@MgAl-LDH particles.
[0042] S4. Add 0.125 parts of KH-570 to 30 parts of an ethanol / water mixture (mass ratio 3:1), adjust the pH to 5.0 with dilute acetic acid, and pre-hydrolyze for 30 min; add ADP@PDA@MgAl-LDH particles, and perform surface functionalization treatment by stirring at 55℃ for 3.5 h; centrifuge at 4000 r / min for 5 min, wash twice with an ethanol / water mixture and once with deionized water, and vacuum dry at 65℃; disperse the dried particles in 100 parts of deoxygenated water, deoxygenate by purging with N2 for 25 min and heat to 63℃ to obtain a particle dispersion; pre-add 0.824 parts of AA to 0.762 parts of a 30% NaOH solution to neutralize AA to 50%, and add 0.576 parts of... HEMA (AA to HEMA mass ratio of 1:0.7, total mass of AA and HEMA 1.4 parts) was mixed with 0.0245 parts PEGDA (total mass of AA and HEMA 1.75%) to obtain monomer solution; 0.0105 parts ammonium persulfate (total mass of AA and HEMA 0.75%) was prepared into a 10% ammonium persulfate aqueous solution; the monomer solution and the initiator aqueous solution were slowly added dropwise to the particle dispersion over a period of 1.75 h; after the addition was completed, the reaction was continued at the temperature for 2.5 h; after the reaction was completed, the mixture was centrifuged at 4500 r / min for 10 min, washed repeatedly with deionized water until the pH of the washing solution was 6.5-7.5, and vacuum dried at 65℃ until the moisture content was no higher than 0.2% to obtain flame retardant particles.
[0043] A2. Preparation of Flame-Retardant Functional Layer Material: Flame-retardant particles were vacuum dried at 65℃ until the moisture content was ≤0.2%; KH-550 surface-modified magnesium hydroxide was dried at 85℃ until the moisture content was ≤0.3%; 34 parts of the dried flame-retardant particles were premixed with 12 parts of EVA, 6 parts of maleic anhydride-grafted polyethylene, 0.15 parts of antioxidant 1010, and 0.15 parts of antioxidant 168, and the premixed material was vacuum dried again at 65℃ until the moisture content was ≤0.05% to obtain a pre-dispersion material; then 60 parts of LLDPE, the remaining 28 parts of EVA, the remaining 0.15 parts of antioxidant 1010, and the remaining 0.15 parts of antioxidant 168 were mixed. 0.17 parts of calcium stearate, 0.65 parts of calcium stearate, and 2.5 parts of carbon black masterbatch were added from the main feed port of the twin-screw extruder; the above pre-dispersed material and 48 parts of dried KH-550 surface-modified magnesium hydroxide were added from the middle and rear side feed port; the temperature settings of each zone of the twin-screw extruder were as follows: Zone 1 130℃, Zone 2 140℃, Zone 3 150℃, Zone 4 155℃, Zone 5 155℃, Zone 6 150℃, and die head 145℃, screw speed 300 rpm, and actual melt temperature 162℃. The material was melt-blended, extruded, water-cooled, and pelletized to obtain a flame-retardant functional layer material. The obtained flame-retardant functional layer material was vacuum-dried at 60-70℃ until the moisture content was ≤0.05%, sealed and stored, and used for co-extrusion of the outer sheath.
[0044] The flame-retardant functional layer formulation is as follows: 60 parts LLDPE, 40 parts EVA, 34 parts flame-retardant particles, 48 parts KH-550 surface-modified magnesium hydroxide, 6 parts maleic anhydride-grafted polyethylene, 0.30 parts antioxidant 1010, 0.32 parts antioxidant 168, 0.65 parts calcium stearate, and 2.5 parts carbon black masterbatch.
[0045] A3. Preparation of outer protective layer material: 80 parts of LLDPE, 20 parts of EVA, 5.5 parts of carbon black masterbatch, 0.3 parts of antioxidant 1010, 0.3 parts of antioxidant 168, and 0.5 parts of calcium stearate were added to a high-speed mixer and mixed for 5 minutes; the mixture was then melt-blended and granulated using a twin-screw extruder. The temperatures of each zone of the twin-screw extruder were set as follows: Zone 1 130℃, Zone 2 140℃, Zone 3 150℃, Zone 4 150℃, Zone 5 150℃, and Die head 145℃. The actual melt temperature did not exceed 160℃, thus obtaining the outer protective layer material.
[0046] A4. Medium-voltage power cable manufacturing: A conductor shielding layer, an XLPE insulation layer, and an insulation shielding layer are sequentially extruded onto a copper conductor, and the three layers are co-extruded and cross-linked to form the core. Semi-conductive water-blocking tape (20% overlap) is wrapped around the core, and then copper tape is overlapped to form a metal shielding layer with an overlap rate ≥15%. A PE inner sheath is extruded over the metal shielding layer. A double-layer steel tape armor layer is wrapped over the inner sheath, and then water-blocking tape is wrapped around the armor layer with an overlap rate ≥20%. The water-blocking tape uses polyester fiber nonwoven fabric as the base material, and the coating is low-crosslinked acrylic-acrylic acid. The sodium copolymer has a thickness of 0.4 mm; its free water absorption ratio in deionized water is 25 times, its expansion height after 30 seconds of water absorption is 2.5 mm, and its water absorption under 0.1 MPa pressure is not less than 12 times its dry weight; finally, the flame-retardant functional layer material and the outer protective layer material are co-extruded to form the outer sheath layer. During co-extrusion, the temperature of each zone of the extruder used for the flame-retardant functional layer and the outer protective layer is set to 150℃, and the die head temperature is 150℃; in this embodiment, the total thickness of the outer sheath layer is 26 / 35kV, 240 mm according to GB / T12706.3-2020. 2 The cable is specified to be 3.5mm thick, with a flame-retardant functional layer thickness of 2.45mm and an outer protective layer thickness of 1.05mm. The flame-retardant functional layer is located inside the outer protective layer. After cooling, printing, and coiling, the medium-voltage power cable is obtained.
[0047] This embodiment prepares a conductor with a rated voltage of 26 / 35kV and a nominal conductor cross-sectional area of 240mm². 2 For medium-voltage power cables, except for the water-blocking layer and outer sheath layer specifically defined in this application, the remaining structural dimensions shall be set in accordance with the relevant requirements of GB / T 12706.3-2020.
[0048] Example 2
[0049] The difference from Example 1 is that the amount of flame retardant particles used in the flame retardant functional layer is 30 parts, while the rest of the preparation method is the same as in Example 1.
[0050] Example 3
[0051] The difference from Example 1 is that the amount of flame retardant particles used in the flame retardant functional layer is 38 parts, while the rest of the preparation method is the same as in Example 1.
[0052] Example 4
[0053] The difference from Example 1 is that the molar ratio of Mg to Al in the metal salt mixed solution in S3 is 2.4:1, that is, Mg(NO3)2·6H2O is 1.517 parts. The rest of the preparation method is the same as in Example 1.
[0054] Example 5
[0055] The difference from Example 1 is that the molar ratio of Mg to Al in the metal salt mixed solution in S3 is 2.6:1, that is, Mg(NO3)2·6H2O is 1.644 parts. The rest of the preparation method is the same as in Example 1.
[0056] Example 6
[0057] The difference from Example 1 is that in S4, the mass ratio of AA to HEMA is 1:0.6, that is, the total mass of AA and HEMA remains unchanged at 1.4 parts, of which AA is 0.875 parts and HEMA is 0.525 parts. 0.875 parts of AA are added to 0.809 parts of NaOH solution with a mass concentration of 30% in advance to make the neutralization degree of AA 50%. The rest of the preparation method is the same as in Example 1.
[0058] Example 7
[0059] The difference from Example 1 is that in S4, the mass ratio of AA to HEMA is 1:0.8, that is, the total mass of AA and HEMA remains unchanged at 1.4 parts, of which AA is 0.778 parts and HEMA is 0.622 parts. 0.778 parts of AA are added to 0.720 parts of NaOH solution with a mass concentration of 30% in advance to make the neutralization degree of AA 50%. The rest of the preparation method is the same as in Example 1.
[0060] Example 8
[0061] The difference from Example 1 is that the amount of LLDPE in the outer protective layer is 70 parts and the amount of EVA is 30 parts, while the rest of the preparation method is the same as in Example 1.
[0062] Comparative Example
[0063] Comparative Example 1
[0064] The difference from Example 1 is that flame-retardant particles are not used in the flame-retardant functional layer; instead, uncoated raw ADP is used. The amount of raw ADP added is based on the same mass as the ADP core contained in the flame-retardant particles in Example 1. The actual total mass of each coating layer (PDA layer, MgAl-LDH layer, and AA-HEMA polymer layer) in the flame-retardant particles is determined by the actual weight gain of the dried products in each step of the flame-retardant particle preparation process in Example 1: the dried mass of the ADP core, ADP@PDA particles, ADP@PDA@MgAl-LDH particles, and the final flame-retardant particles are weighed respectively, and the total mass of the coating layer is calculated by summing the weight gain of each step. The same mass of matrix resin (LLDPE / EVA according to the flame-retardant functional layer matrix ratio) is added in Comparative Example 1 to maintain the consistency of the total mass of the formulation and to ensure that the mass of the ADP core contained in each group is the same. The rest of the preparation method is the same as in Example 1.
[0065] Comparative Example 2
[0066] The difference from Example 1 is that, instead of forming an AA-HEMA polymer layer on the ADP@PDA@MgAl-LDH surface through KH-570 surface functionalization and in-situ polymerization, ADP@PDA@MgAl-LDH particles are physically mixed with AA-HEMA crosslinking polymer pre-prepared according to the same monomer ratio as in Example 1, so that the theoretical feed amount of each raw material is consistent with the feed amount of the corresponding coating step in Example 1; the actual amount of AA-HEMA crosslinking polymer added is based on the actual recovered mass after drying; the AA-HEMA crosslinking polymer is prepared by the following method: 0.824 parts of AA are mixed with 0.762 parts of a polymer with a mass concentration of... Partial neutralization to 50% neutralization was achieved using a 30% NaOH solution. 0.576 parts HEMA and 0.0245 parts PEGDA were added, along with an appropriate amount of deionized water and N2 purging for 25 minutes to remove oxygen. The temperature was raised to 63°C, and 0.0105 parts ammonium persulfate (prepared as a 10% aqueous solution) were added dropwise over 1.75 hours. After the addition was complete, the reaction continued for another 2.5 hours. After the reaction, the mixture was filtered, washed with deionized water until the pH of the washing solution reached 6.5–7.5, and vacuum dried at 65°C until the moisture content was no higher than 0.2%. The mixture was then freeze-pulverized and sieved to achieve a D50 of 1–2 μm, yielding the AA-HEMA crosslinked polymer. The remaining preparation methods were the same as in Example 1.
[0067] Comparative Example 3
[0068] The difference from Example 1 is that the flame-retardant particles only coat the LDH layer, i.e., ADP@PDA@MgAl-LDH particles; the amount of these particles added is based on the same mass as the ADP core contained in the flame-retardant particles in Example 1; the actual mass of the AA-HEMA polymer layer is determined by the difference in the dry mass between the final flame-retardant particles and the ADP@PDA@MgAl-LDH particles in Example 1; the same mass of matrix resin (LLDPE / EVA according to the flame-retardant functional layer matrix ratio) is added to maintain the consistency of the total filling amount and total mass of the sample; the rest of the preparation method is the same as in Example 1.
[0069] Comparative Example 4
[0070] The difference from Example 1 is that the water-blocking tape is not wrapped around the outside of the armor layer, but the rest of the preparation method is the same as that of Example 1.
[0071] The flame-retardant functional layer material particles obtained in Examples 1-7 and Comparative Examples 1-3 were hot-pressed on a flat vulcanizing machine at 150-155°C and 15 MPa for 5-8 minutes. They were then held at 10 MPa and cooled to room temperature, and cut into sheets with thicknesses of 1 mm, 3 mm, and 4 mm, as well as standard dumbbell-shaped test pieces. Samples of corresponding thicknesses were selected according to the test items for oxygen index, vertical combustion, cone calorimetry, tensile strength, elongation at break, volume resistivity, total phosphorus concentration in the leachate, and performance retention before and after immersion in water. The flame-retardant functional layer materials of Examples 1-8 and Comparative Examples 1-3 were hot-pressed with their corresponding outer protective layer materials into sheets, and then hot-pressed together at 150°C and 15MPa to achieve a flame-retardant functional layer thickness of 1.75mm, an outer protective layer thickness of 0.75mm, and a total thickness of 2.50mm, with the flame-retardant functional layer accounting for 70% of the total thickness. These were then cut into 100mm × 100mm samples, with an artificial slit pre-fabricated in the center for sheath slit sealing performance testing. Complete finished cable samples from Examples 1-3, Example 8, Comparative Examples 1 and 3 were subjected to bundled burning tests; complete finished cable samples from Examples 1 and 4 were subjected to longitudinal water-blocking performance tests. The performance test results are shown in Tables 1 and 2, respectively.
[0072] Performance Test 1
[0073] The oxygen index (LOI) was tested according to GB / T 2406.2-2009. The sample size was 120mm×10mm×4mm, and it was made of flame-retardant functional layer material by molding or injection molding. The test was carried out at room temperature (23±2℃), with an oxygen concentration adjustment step of 0.2%. At least 5 samples were tested for each sample. The test results were expressed as oxygen index (%) by volume percentage and retained to one decimal place.
[0074] Performance Test 2
[0075] The vertical flammability rating was tested according to Method B (vertical flammability method) in GB / T 2408-2021. The sample size was 125mm×13mm×3mm. A Bunsen burner flame with a flame height of 20mm and a blue inner flame was used. The sample was ignited twice, with each ignition time being 10s. Five samples were tested in each group. The V-0, V-1, and V-2 flammability ratings were evaluated based on indicators such as the flaming time, whether the dripping material ignited the absorbent cotton, and whether the flame spread to the fixture.
[0076] Performance Test 3
[0077] The cone calorimetry test was conducted according to GB / T 16172-2026. The sample size was 100mm×100mm×3mm, and three parallel samples were tested in each group. The samples were conditioned at 23±2℃ and 50±5% relative humidity for at least 48 hours before testing. During testing, the sample was placed horizontally with the radiation cone positioned above it, and the thermal radiation flux was set to 50kW / m². 2 Electric spark ignition was used. The non-exposed surfaces (i.e., the bottom and sides of the sample) were covered with aluminum foil, exposing only the upper surface to radiation. The peak heat release rate (pHRR, kW / m²) was recorded. 2 Total heat release (THR, MJ / m³) 2 The results were calculated as the arithmetic mean of three parallel samples and the ignition time (TTI, s).
[0078] Performance Test 4
[0079] Tensile strength and elongation at break were tested in accordance with GB / T 1040.2-2022. The specimens were 1BA type dumbbell specimens, the test speed was 50 mm / min, the gauge length was 25 mm, and the test environment temperature was 23±2℃. Five specimens were tested in each group, and the average values of tensile strength (MPa) and elongation at break (%) were calculated.
[0080] Performance Test 5
[0081] Volume resistivity was tested according to GB / T 31838.2-2019. The sample was a circular disc with a diameter of 100 mm and a thickness of 1 mm. Before testing, the sample was pretreated at 23±2℃ and 50±5% relative humidity for at least 24 hours. A three-electrode system was used: the measuring electrode had a diameter of 50 mm, the protective electrode had an inner diameter of 54 mm and an outer diameter of 74 mm, and the high-voltage electrode had a diameter of not less than 80 mm. A DC voltage of 500 V was applied, and the charging time was 60 s. The test environment temperature was 23±2℃ and the relative humidity was 50±5%. The test results are expressed in Ω·cm, and the geometric mean of the test values of three samples is taken.
[0082] Performance Test 6
[0083] The total phosphorus concentration in the leachate was tested using a self-made impregnation method. The sample size was a 50mm × 50mm × 3mm square, with three parallel samples per group. After weighing, the samples were placed in a sealed stainless steel impregnation vessel lined with polytetrafluoroethylene (PTFE). Deionized water was added at a water-to-sample mass ratio of 50:1. The vessel was then sealed and placed in a constant temperature oven at 80±1℃ for 168 hours. After the specified time, the impregnation vessel was removed, cooled to 23±2℃, and shaken well. The supernatant was collected, and potassium persulfate solution was added. The mixture was then pressure digested at 120℃ for 30 minutes to convert various forms of phosphorus into orthophosphate. After cooling, the absorbance was measured at 700nm using the ammonium molybdate-ascorbic acid spectrophotometric method (referencing GB / T 11893-1989). A reagent blank was set up simultaneously, and a standard curve was established using a series of phosphate standard solutions. When the total phosphorus concentration in the digestion solution exceeded the linear range of the standard curve, it was quantitatively diluted with deionized water to the linear range for determination, and the total phosphorus concentration of the original leachate was calculated according to the dilution factor. The sample results were calculated after blank correction and expressed in mg / L. The method phosphorus detection limit was 0.02 mg / L. A separate 120 mm × 10 mm × 4 mm oxygen index sample was prepared and soaked in deionized water at 80 ± 1 °C for 168 h at the same water / sample mass ratio. After removal, it was humidified according to regulations, and the oxygen index after aging was determined according to GB / T2406.2-2009. The flame retardant retention rate (the ratio of the LOI after aging to the original LOI, expressed as a percentage) was calculated.
[0084] Performance Test 7
[0085] The sealing performance of the sheath crack (simulating radial water resistance) was tested using a self-made sheath crack leakage test device. The device included a constant-pressure water tank, a sample holder, and a metering collector. The constant-pressure water tank was connected to a compressed air source via a pneumatic pressure regulating valve, with a pressure control accuracy of ±0.005 MPa and a test pressure set at 0.1 MPa. The sample holder consisted of two stainless steel flange plates, with a 50 mm diameter water passage hole in the center of each flange. An O-ring silicone rubber seal was embedded on the inner side of the flange. The sample was placed between the two flanges and evenly tightened with bolts. The bolt torque was set to 2.5 N·m, and the bolts were tightened diagonally so that the outer protective layer of the sample faced the pressurized water side, while the inner side (flame-retardant functional layer) was open to the atmosphere. The leaked liquid was continuously collected in a container placed on an electronic balance with a resolution of 0.01 g. The leakage mass was continuously recorded and converted to volume. Artificial cracks were created at the center of the specimen using a standard scriber (60° tip angle, 0.1mm tip curvature radius). The crack length was 5±0.2mm, and the depth penetrated the sheath specimen. After scriber creation, a 0.10mm thick polyester film was inserted into the crack and then removed. The opening at the center of the crack was measured using a stereomicroscope. Specimens with an initial opening of 0.10±0.01mm were selected for testing. The water temperature was 23±2℃. Five parallel samples were set up for each group. The sealing time (from the application of water pressure to the last visible droplet; after the last droplet appeared, water pressure was maintained for 60s, and sealing was confirmed when no droplets leaked out for 60s; the confirmation observation time was not included in the sealing time, unit: s) and the total leakage (the total leakage water volume collected from the application of water pressure to the completion of sealing, unit: mL) were recorded for each parallel sample. The results are expressed as an arithmetic mean. The maximum pressure recording time is 600 seconds; if leakage stops before 600 seconds, continue to maintain water pressure and observe for another 60 seconds for confirmation. If leakage does not stop within 600 seconds or the cumulative leakage reaches 50 mL, it is considered that the sealing is not complete.
[0086] Performance Test 8
[0087] Changes in electrical and mechanical properties before and after immersion: Volume resistivity and tensile specimens were immersed in deionized water at 60℃ for 168h. After immersion, the specimens were removed, the surface water was wiped dry with clean filter paper, and the specimens were conditioned in an environment of 23±2℃ and 50±5%RH for 24h. The volume resistivity, tensile strength, and elongation at break of the specimens were then tested. The retention rates of volume resistivity, tensile strength, and elongation at break were calculated, which are the ratios of the test values after immersion to the test values before immersion, expressed as percentages, to evaluate the performance stability of the material in a humid environment.
[0088] Performance Test 9
[0089] Cable Bundle Combustion Test: The test shall be conducted in accordance with GB / T 18380.35-2022. The number of test specimens shall be calculated based on the volume of non-metallic material per meter of a single cable, so that the nominal volume of non-metallic material in the bundled specimens reaches 1.5 L / m (Class C), and the specimens shall be arranged and installed in accordance with the provisions of GB / T18380.35-2022. The length of the finished cable specimen shall be 3.5 m; the burner and gas flow rate shall be in accordance with GB / T18380.31-2022, and the ignition time shall be 20 min; the maximum char height (m), whether the flame extends to the top, and the duration of dripping combustion (s) shall be recorded to evaluate whether the specimen passes the Class C bundle combustion test.
[0090] Performance Test 10
[0091] Longitudinal water-blocking performance of finished cables: Three sections of finished cables from Example 1 and Comparative Example 4 were taken, each section being 1.2m in length. The outer surface of the non-water-inlet end (the end furthest from the test end) and the outer sheath surface of the cable approximately 100mm from the water-inlet end of each section were cleaned and sealed with heat-shrink tubing and sealant. A section approximately 50mm long was cut off from one end of each cable along a direction perpendicular to the cable axis, forming a flat, complete full-section water-inlet end. The outer sheath, water-blocking layer, armor layer, and other structures of the remaining sample must not be peeled off axially. The penetration distance is measured from the newly formed water-inlet end. Except for this water-inlet end, the rest of the cable's outer surface remains sealed. The water-inlet end was vertically immersed downwards into a tank containing deionized water, with the water-inlet end 50mm below the water surface. The rest of the cable remained above the water surface without contact with water. The water temperature was 23±2℃, and the test lasted for 168 hours. After the specified time has elapsed, the sample is removed, its outer surface is dried, and it is cut open along the cable axis starting from the water inlet end face. Each structural layer and the interface between layers are observed separately. The farthest axial distance from any visible water mark to the water inlet end face is taken as the maximum longitudinal permeation distance of the sample, expressed in mm. Three parallel samples are used in each group, and the results are expressed as the arithmetic mean.
[0092] Performance Test 11: Water Absorption Performance Test of Water-Blocking Tape
[0093] The free water absorption ratio, 30s expansion height, and 0.1MPa pressure water absorption of the water-blocking strip were determined by the following methods.
[0094] (1) Free water absorption ratio: Take a water-blocking tape sample and cut it into three square samples of 100mm×100mm. Place the sample in a forced-air drying oven at 105±2℃ and dry it to constant weight (the difference between two consecutive weighings should not exceed 0.1%). Cool it to room temperature in a desiccator and weigh it with a balance with an accuracy of 0.001g, and record it as the dry mass m0. Immerse the sample completely in deionized water at 23±2℃ and let it stand for 60min to allow the sample to reach water saturation. Take out the sample, quickly absorb the water adhering to the surface with filter paper, weigh it immediately, and record it as the wet mass m1. The free water absorption ratio is calculated by the following formula: Free water absorption ratio = (m1–m0) / m0. Take the arithmetic mean of the three samples as the result.
[0095] (2) 30s expansion height: Take a water-blocking tape sample and cut it into three 50mm×50mm square samples. Dry them to constant weight using the method described above. At 23±2℃, place the sample horizontally on a flat glass plate and slowly add deionized water to the center of the sample using a dropper. The amount added should be sufficient to completely wet the sample but not excessively spread. Starting from the beginning of water addition, measure the thickness of the center part of the sample with a vernier caliper or a thickness gauge with an accuracy of not less than 0.01mm at 30s. Subtract the dry thickness to obtain the 30s expansion height. Take the arithmetic mean of the three samples.
[0096] (3) Water absorption under 0.1 MPa pressure: Take a water-blocking tape sample, cut it into three square samples of 100 mm × 100 mm, dry them to constant weight as described above, and record the dry mass as m0. Place the sample between two porous stainless steel plates. The effective pressure-bearing area of the porous plates is 100 mm × 100 mm, and the pore diameter is 1-2 mm. Apply uniform pressure to the porous plates so that the sample is subjected to a pressure of 0.1 MPa. At the same time, immerse the entire pressure-bearing device in deionized water at 23 ± 2 °C so that the water can fully contact the sample through the porous plates. Maintain the pressure and immersion state for 60 min. Depressurize and take out the sample. Quickly absorb the water adhering to the surface with filter paper and weigh it immediately. Record the mass after pressure absorption as m2. The water absorption under pressure is calculated by the following formula: Water absorption under pressure = (m2 – m0) / m0. Take the arithmetic mean of the three samples.
[0097] Table 1. Test results of flame-retardant functional layer material properties
[0098]
[0099] Table 2. Results of crack sealing in simulated double-sheathed samples and performance tests on finished cables.
[0100]
[0101] Note: * indicates the recorded value at which the test was terminated when the cumulative leakage reached the termination threshold (50mL); "—" indicates no test was conducted. The flame-retardant functional layer of Example 8 had the same formulation as that of Example 1, and the single-material performance test of the flame-retardant functional layer was not repeated. It only participated in the double-layer sheath crack sealing and finished cable bundle burning test. Comparative Example 4 only participated in the longitudinal water-blocking performance test of the finished cable.
[0102] As can be seen from Examples 1-3, within the range of core-shell flame retardant particle dosage, the oxygen indices of Examples 1, 2, and 3 are 32.4%, 31.0%, and 33.1%, respectively, all remaining above 30%, and all achieving V-0 rating in vertical combustion. This indicates that the present invention exhibits a high oxygen index and achieves V-0 rating under the stated test conditions within the range of 30-38 parts of flame retardant particle addition. Furthermore, with the increase of flame retardant particle dosage, the oxygen index and peak heat release rate generally show an improving trend, but the changes are not strictly linear; for example, the pHRR of Example 2 is 248 kW / m³. 2 Examples 1 and 3 are 218 kW / m², respectively. 2 and 207kW / m 2 This indicates that flame retardant efficiency is also affected by the combined effects of particle dispersion state and inorganic-organic interface interaction.
[0103] Comparing Examples 1 with Examples 4 and 5, it can be seen that when the Mg / Al molar ratio varies within the range of 2.4 to 2.6:1, the oxygen indices of Examples 4, 1, and 5 are 31.5%, 32.4%, and 32.7%, respectively, and the peak heat release rates are 236, 218, and 212 kW / m³, respectively. 2 Although the flame retardant and mechanical properties of the three substances differ, they are all at a relatively good level, indicating that the corresponding comprehensive flame retardant and mechanical properties can be obtained when the Mg / Al molar ratio is 2.4 to 2.6.
[0104] Comparing Examples 1 with Examples 6 and 7, it can be seen that when the AA / HEMA mass ratio varies within the range of 1:0.6 to 1:0.8, the oxygen indices of Examples 6, 1, and 7 are 31.8%, 32.4%, and 32.9%, respectively, and their flame retardant performance is similar. All of them reach V-0 rating in vertical burning, indicating that the differences in flame retardant performance test results among the groups are relatively small within this test range. As the proportion of HEMA increases, the elongation at break and its retention rate after immersion in water show an upward trend.
[0105] Examples 1 and 8 show that the tested 80 / 20 and 70 / 30 outer protective layer ratios can maintain the corresponding crack sealing and bundle combustion performance.
[0106] Comparing Examples 1-8 with Comparative Examples 1-4, it can be seen that: Comparative Example 1, without ADP coating, had a phosphorus leaching amount as high as 27.9 mg / L, a flame retardant retention rate of only 80.9%, and the crack was not sealed within 600s with a leakage of 50.0 mL; Comparative Example 2, which physically mixed ADP@PDA@MgAl-LDH with AA-HEMA polymer, had a phosphorus leaching amount reduced to 16.8 mg / L, a crack sealing time of 520s, but a total leakage of 45.3 mL. The phosphorus leaching amount of Comparative Example 2 was higher than that of Comparative Example 3, which only coated the LDH layer, possibly because the physically mixed polymer did not form a continuous surface barrier layer, and the water absorption channels at the interface may have increased. Example 1 had a phosphorus leaching amount of 4.2 mg / L, a crack sealing time of 48s, and a total leakage of 3.1 mL, all of which were lower than those of Comparative Examples 1-3 in the above comparisons. Furthermore, Comparative Example 4, without a water-blocking layer, showed a penetration length of 148 mm in a 168-hour longitudinal water penetration test, while Example 1 showed 12 mm. These results indicate that under the test conditions, the hierarchical structure of the flame-retardant particles and the double-layer sheath design of this application reduce the total phosphorus concentration in the hot water leachate, shorten the time required to stop visible dripping under the artificial crack and water pressure conditions, and reduce the longitudinal water penetration length of the finished cable, demonstrating its potential for further application in humid or potentially immersion environments.
[0107] Figure 1 This is a schematic diagram of the cross-sectional structure of the medium-voltage power cable of the present invention. Conductor 1 is the current-carrying core of the cable. Conductor shielding layer 2, insulation layer 3, and insulation shielding layer 4 are sequentially wrapped around conductor 1 to form the conductor core. Semiconductor water-resistant tape 5 is wrapped around insulation shielding layer 4, metal shielding layer 6 is wrapped around semiconductor water-resistant tape 5, inner sheath 7 is extruded around metal shielding layer 6, and armor layer 8 is wrapped around inner sheath 7. Water-blocking layer 9 is wrapped around armor layer 8 to inhibit the longitudinal diffusion of moisture along the cable. The outer sheath consists of an inner flame-retardant functional layer 10 and an outer protective layer 11, with the thickness of flame-retardant functional layer 10 accounting for 68% to 75% of the total thickness of the outer sheath. Figure 1 In the structure shown, each layer is arranged sequentially from the inside out.
[0108] Figure 2 This is a schematic diagram of the hierarchical structure of the flame-retardant particles of the present invention. The PDA intermediate layer 14 coats the surface of the ADP core 15, the MgAl-LDH layer 13 is formed in situ through a template of the PDA intermediate layer 14, and the AA-HEMA polymer layer 12 coats the surface of the MgAl-LDH layer 13. Figure 2 The coating layers shown are for illustrative purposes only and do not represent actual thickness ratios. The PDA intermediate layer 14 is crosslinked with genipin, the MgAl-LDH layer 13 is surface-functionalized with KH-570, and the AA-HEMA polymer layer 12 is formed by copolymerizing pre-partially neutralized acrylic acid with hydroxyethyl methacrylate and crosslinked with PEGDA.
[0109] The above results demonstrate and describe the basic principles and main features of this application, as well as its advantages.
[0110] Those skilled in the art should understand that this application is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of this application. Various changes and modifications can be made to this application without departing from the spirit and scope thereof, and all such changes and modifications fall within the scope of this application as claimed. The scope of protection of this application is defined by the equivalents of the appended claims.
Claims
1. A medium-voltage power cable, comprising, from the inside out, a conductor, a conductor shielding layer, an insulation layer, an insulation shielding layer, a semi-conductive water-resistant tape, a metallic shielding layer, an inner sheath, an armor layer, a water-blocking layer, and an outer sheath, characterized in that: The outer sheath layer includes a flame-retardant functional layer and an outer protective layer arranged sequentially from the inside to the outside; Based on 100 parts by weight of linear low-density polyethylene and ethylene-vinyl acetate copolymer, the flame-retardant functional layer comprises: 58-62 parts of linear low-density polyethylene, the balance being ethylene-vinyl acetate copolymer, 30-38 parts of flame-retardant particles, 45-52 parts of KH-550 surface-modified magnesium hydroxide, 5.5-6.5 parts of maleic anhydride-grafted polyethylene, 0.25-0.35 parts of antioxidant 1010, 0.25-0.4 parts of antioxidant 168, 0.5-0.8 parts of calcium stearate, and 2-3 parts of carbon black masterbatch; The flame-retardant particles include an ADP core, a PDA intermediate layer coated on the surface of the ADP core, a MgAl-LDH layer deposited on the surface of the PDA intermediate layer, and an AA-HEMA polymer layer formed by in-situ polymerization on the surface of the MgAl-LDH layer and bonded to its surface, which is formed by copolymerization of pre-partially neutralized AA and HEMA. The PDA intermediate layer is cross-linked with genipin; the MgAl-LDH layer is surface functionalized with KH-570. The thickness of the flame-retardant functional layer accounts for 68% to 75% of the total thickness of the outer sheath layer; The water-blocking layer is a water-blocking tape containing sodium polyacrylate superabsorbent resin.
2. The medium-voltage power cable according to claim 1, characterized in that, The ethylene-vinyl acetate copolymer has a vinyl acetate content of 18%–28% and a melt flow rate of 3–8 g / 10 min at 190°C and 2.16 kg; the linear low-density polyethylene has a melt flow rate of 1–3 g / 10 min at 190°C and 2.16 kg; the maleic anhydride-grafted polyethylene has a grafting rate of 0.8%–1.2%; and the carbon black masterbatch has a carbon black mass fraction of 40%–50%.
3. The medium-voltage power cable according to claim 1, characterized in that, The D50 of the ADP core is 5-10 μm; the molar ratio of Mg to Al in the MgAl-LDH layer is (2.4-2.6):1; the AA neutralization degree of the AA-HEMA polymer layer is 48%-52%, and the mass ratio of AA to HEMA is 1:(0.6-0.8) based on the mass of AA before neutralization, and it is crosslinked with PEGDA at a mass of 1.5%-2.0% of the total mass of AA and HEMA.
4. The medium-voltage power cable according to claim 1, characterized in that, Based on 100 parts by weight of linear low-density polyethylene and ethylene-vinyl acetate copolymer, the outer protective layer comprises: 70-85 parts of linear low-density polyethylene, the balance being ethylene-vinyl acetate copolymer, 0.2-0.4 parts of antioxidant 1010, 0.2-0.4 parts of antioxidant 168, 0.3-0.8 parts of calcium stearate, and 5-6 parts of carbon black masterbatch.
5. The medium-voltage power cable according to claim 1, characterized in that, The substrate of the water-blocking tape is a polyester fiber nonwoven fabric, and the coating is an acrylic-sodium acrylate copolymer with a thickness of 0.3-0.5 mm. The water-blocking tape has a free water absorption ratio of 15-40 times in deionized water, an expansion height of 1.5-4.0 mm when the water absorption time is 30 s, and a water absorption capacity of not less than 8 times the dry mass under a pressure of 0.1 MPa.
6. A method for manufacturing a medium-voltage power cable as described in any one of claims 1 to 5, characterized in that, Includes the following steps: Flame-retardant particles were vacuum dried at 60–70°C until the moisture content was ≤0.2%; KH-550 surface-modified magnesium hydroxide was dried at 80–90°C until the moisture content was ≤0.3%. Based on 100 parts by weight of linear low-density polyethylene and ethylene-vinyl acetate copolymer, 30-38 parts of dried flame-retardant particles were premixed with 10-15 parts of ethylene-vinyl acetate copolymer, all maleic anhydride-grafted polyethylene, 0.1-0.2 parts of antioxidant 1010, and 0.1-0.2 parts of antioxidant 168. After premixing, the mixture was vacuum dried again until the moisture content was ≤0.05% to obtain a pre-dispersion. Then, 58-62 parts of linear low-density polyethylene, The remaining ethylene-vinyl acetate copolymer, remaining antioxidant 1010, remaining antioxidant 168, 0.5-0.8 parts of calcium stearate, and 2-3 parts of carbon black masterbatch are added from the main feed port of the twin-screw extruder. The pre-dispersed material and dried KH-550 surface-modified magnesium hydroxide are added from the middle and rear side feed port. The mixture is melt-blended and granulated at a temperature of 130-160°C in each zone of the twin-screw extruder, with the actual melt temperature not exceeding 165°C, to obtain the flame-retardant functional layer material. 70-85 parts of linear low-density polyethylene, 15-30 parts of ethylene-vinyl acetate copolymer, 0.2-0.4 parts of antioxidant 1010, 0.2-0.4 parts of antioxidant 168, 0.3-0.8 parts of calcium stearate, and 5-6 parts of carbon black masterbatch are melt-blended, with the total amount of linear low-density polyethylene and ethylene-vinyl acetate copolymer being 100 parts, to obtain the outer protective layer material; A conductor shielding layer, an insulation layer, and an insulation shielding layer are sequentially extruded onto the conductor, and the three layers are co-extruded and cross-linked to form a wire core. A semi-conductive water-resistant tape is wrapped around the wire core, followed by a metal shielding layer. An inner sheath is then extruded over the metal shielding layer. An armor layer is then wrapped over the inner sheath, and a water-blocking layer is wrapped around the armor layer, with an overlap rate of ≥15%. Finally, the flame-retardant functional layer material and the outer protective layer material are co-extruded to form an outer sheath layer at an extrusion temperature of 140–165°C. The flame-retardant functional layer is located inside the outer protective layer, thus obtaining the medium-voltage power cable.
7. The method for preparing a medium-voltage power cable according to claim 6, characterized in that, The method for preparing the flame-retardant particles includes the following steps: S1, by weight, 10 parts of ADP are subjected to air jet milling and classification to make D50 5-10 μm; the classified ADP is surface silanized and modified with 0.15-0.25 parts of KH-550 in 30-40 parts of ethanol / water mixed solvent, and after the reaction, the particles are filtered, washed and dried to obtain the ADP core; S2. Disperse the ADP cores obtained in S1 in 180–220 parts of Tris buffer; add 0.6–0.8 parts of dopamine hydrochloride, stir for 12–16 h at 20–25 °C in contact with air, filter, wash until the supernatant is clear, redisperse the particles in 180–220 parts of deionized water, add 0.02–0.03 parts of genipin for crosslinking for 4–6 h, wash again to obtain ADP@PDA particles; S3. Disperse the ADP@PDA particles obtained in S2 in 180–220 parts of deionized water to obtain a particle dispersion. Dissolve 0.9–0.95 parts of Al(NO3)3·9H2O and Mg(NO3)2·6H2O calculated according to the Mg / Al molar ratio of 2.4–2.6:1 in 60–80 parts of deionized water to obtain a metal salt mixed solution. Prepare an alkaline solution containing 1–1.5 mol / L NaOH and 0.1–0.2 mol / L Na2CO3, with the actual amount of alkaline solution added determined by pH feedback. Under N2 protection and at 60–65℃, add the metal salt mixed solution and alkaline solution dropwise in parallel to the particle dispersion, stabilizing the pH at 9.3–9.7 by adjusting the alkaline solution flow rate. After the addition is complete, age the solution, wash until the filtrate is nearly neutral, and dry to obtain ADP@PDA@MgAl-LDH particles. S4. The ADP@PDA@MgAl-LDH particles obtained in S3 are surface-functionalized with 0.1-0.15 parts of KH-570, dispersed in 80-120 parts of deoxygenated water, deoxygenated with N2 for 20-30 minutes and heated to 60-65℃; AA is partially neutralized with a 25%-35% NaOH solution to a neutralization degree of 48%-52%, and based on the AA before partial neutralization, it is mixed with HEMA at a mass ratio of 1:(0.6-0.8), with a total mass of AA and HEMA of 1.2-1.6 parts. PEGDA of 1.5%-2% of the total mass of AA and HEMA is added to obtain a monomer solution; the monomer solution and ammonium persulfate aqueous solution are added dropwise to the particle dispersion for 1.5-2 hours, and the reaction continues for 2-3 hours after the addition is completed; after the reaction is completed, the mixture is filtered, washed, and dried to obtain the flame-retardant particles.
8. The method for preparing a medium-voltage power cable according to claim 7, characterized in that, In S1, the mass ratio of ethanol to water in the ethanol / water mixed solvent is 3:1; the pH is adjusted to 4.5-5.5 with dilute acetic acid; KH-550 is pre-hydrolyzed for 20-40 min before ADP is added; the reaction temperature is 50-60℃; and the reaction time is 2-3 h. In S2, the Tris buffer is prepared by tris(hydroxymethyl)aminomethane and hydrochloric acid, with a concentration of 10-30 mmol / L and a pH of 8.3-8.
5.
9. The method for preparing a medium-voltage power cable according to claim 7, characterized in that, In S3, the metal salt mixture and alkali solution are added dropwise in two parallel streams: the first deposition involves adding 50% of the metal salt mixture and alkali solution over 1–1.5 hours, maintaining a pH of 9.3–9.7, aging for 2–3 hours, followed by washing and redispersing the particles in 180–220 parts of deionized water; the second deposition involves adding the remaining metal salt mixture and alkali solution over 1–1.5 hours, maintaining a pH of 9.3–9.7, and aging for 4–6 hours. In S4, KH-570 is first pre-hydrolyzed in an ethanol / water mixture at pH 4.5–5.5 for 20–40 minutes, and then surface functionalized by stirring at 50–60°C for 3–4 hours. The ammonium persulfate aqueous solution has a mass concentration of 5%–15%, and the amount of ammonium persulfate is 0.5%–1% of the total mass of AA and HEMA.
10. An application of a medium-voltage power cable as described in any one of claims 1 to 5, characterized in that, The medium-voltage power cable is used in damp or potentially water-immersed environments such as tunnels, pipe corridors, and shafts, to balance flame retardancy and water resistance.